Fakor-Faktor yang Mempengaruhi Permintaan Konsumen terhadap Buah Jeruk Lokal di Kota Denpasar - ARTAMA, I MADE OKA SURYA; ANTARA, I MADE; DJELANTIK, A.A.A WULANDIRA SAWITRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.5, No.2, April 2016)
Abstract Factors That Affect Consumer Demand Against Local Oranges in Denpasar City This study aims to test the accuracy of demand function model to approach the demand local oranges in Denpasar, identify the factors that affect consumer demand to local oranges in Denpasar, and estimate the elasticity of citrus nobilis demand in Denpasar. Location choosen purposely those in the kreneng market, ketapian market, sanglah market, and badung markets. The population on this research are the buyers of local oranges fruit. Samples taken as many as 50 people use purposive sampling techniques. This research using two demand function models namely linier demand function and Cobb-Douglas demand function who tested with three criteria which resulted the best model. Independent variable that affects was : the price of local oranges (x1), the price of import oranges (x2), the price of apples (x3), the price of mango (x4), family income (x5), and extended family (x6). Cobb-Douglas demand function model namely LnY = 2,912 - 1,109LnX1* - 1,461LnX2* - 1,579LnX3* +1,383LnX4* + 0,622LnX5* + 1,449LnX6*. Factors that affects are the price of local oranges, the price of other fruit (import oranges, apple, mango ), family income, andthe number of family members. Price elasticity on the demand of local oranges is elastic. Complementary goods namely import orange fruit and apples. Substitutiongoods namely mango. Income elasticity showed that local oranges is inelastic. Consumers should choose the local oranges, because more assured quality and isproduced domestically.
Keywords: demand, local oranges, price, elasticity